Establishment and validation of microsampling techniques in wild rodents for ecotoxicological research. Issue 9 (16th May 2018) - Imholt, Christian; Abdulla, Tariq; Stevens, Alexander; Edwards, Peter; Jacob, Jens; Woods, David; Rogers, Elaine; Aarons, Leon; Segelcke, Daniel
Abstract: Compounds and products in the biocide and plant protection sector can only be registered after formal risk assessment to ensure safety for users and the environment. In bird and mammal risk assessment, this is routinely done using generic focal species as models, which are of particular exposure risk. Such a species is the common vole ( Microtus arvalis ) due to its high food intake relative to the low body weight. For wild species, biological samples, data and hence realistic exposure estimations are particularly difficult to obtain. In recent years, advances have been made in the techniques related to serial microsampling of laboratory mice and rats that allow for a reduction in sampling volumes. Similar progress in wild species sampling is missing. This study presents a proof of concept to dose wild rodents with relevant compounds and to draw serial, low volume blood samples suitable for state‐of‐the art toxicokinetic analyses. For the first time, the jugular vein of common voles was used to administer compounds (two frequently used fungicidal components). This procedure and the following microsampling of blood (2 × 10 μl six times within 24 hours) from the lateral tail vein did not affect body weight and mortality of voles. Samples were sufficient to detect dissipation patterns of the compounds from blood in toxicokinetic analysis. These results suggest that microsampling can be well translated from laboratory mice to wild rodent species and help to obtain realistic exposure estimates in wild rodents for ecotoxicological studies as well as to promote the 3R concept in studies with wild rodent species. Abstract : Recent advances with serial microsampling techniques to improve exposure estimation for risk assessment of plant protection compounds need to be adopted for wild species. This study presents a proof of concept to dose wild rodents with relevant compounds and to draw serial, low volume blood samples suitable for toxicokinetic analyses. Samples were sufficient to detect dissipation patterns of the compounds from blood in toxicokinetic analysis. These results suggest that microsampling can be well translated from laboratory mice to wild rodents.